Relationship between in-service teachers-attitude, knowledge, teaching experience and views on the utilization of diagrams in geometry in some selected primary schools in Ibadan, Oyo State (2024)
This study investigated the relationship between in-service teachers ' attitude, knowledge, teaching experience and views on the utilisation of diagrams in geometry in some selected primary schools in Ibadan. Oyo State. Visual-Spatial Intelligence and Multimedia Learning theories were adopted as the framework, while the survey design was used. The purposive sampling technique were used to select 130 public primary school teachers based on their qualification as primary education mathematics certificate. The instruments used were In- Service Teacher Attitude, Teaching Experience, Knowledge and Views on the utilisation of diagrams in geometry questionnaires. Data were analysed using descriptive statistics, Pearson product moment correlation and Multiple regression, at p<0.05. There were positive significant relationships between teachers ’ attitude, knowledge, teaching experience and views on the utilisation of diagrams in geometry. Teachers 'gender was not significant. Teachers ’knowledge and attitude contributed to their utilisation of diagrams in geometry. The study recommended that educational policy makers should emphasis the pedagogical benefits of diagrams in geometry.